Application of Backward Method to Determine the Factor that Affect the Poverty Level of Sibolga City 2011-2020 - Tika Afina Sari (JMEA : Journal of Mathematics Education and Application, 2023)
The level of poverty is a condition that is financially impossible to meet an adequate standard of living of the local community, not only in terms of health and education, but also in terms of basic needs.The purpose of this study is to obtain information about the factors that influence the poverty rate of Sibolga City from 2011-2020 by applying the backward elimination method which sequentially selects variables that do not affect the equation model.The estimators obtained are. The percentage of determination obtained is 83.4% with a significance level of 5 percentand the most influential factor of the independent variables that remain in the equation model is the average length of schooling.